EDUKASI TEKNIK MENYIKAT GIGI DENGAN METODE FONES UNTUK MENINGKATKAN KESEHATAN GIGI DAN MULUT PADA SISWA SDN 23 MARAPALAM PADANG - Nila Kasuma; Haria Fitri; Tiara Adzakiyah (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Oral health issues are of high concern in Indonesia, where the majority of the population faces challenges in this aspect. There is a significant prevalence of dental caries in young children, signaling the complexity of this health issue at the population level. This issue is linked to proper brushing behavior, which is practiced by only a small percentage of the Indonesian population. As a result, children should be educated about oral health, particularly proper brushing techniques, from an early age. The Fones technique, which combines horizontal and circular movements, is one effective technique. This technique is effective for cleaning teeth and maintaining gum health. This educational activity aims to provide the students at State Elementary School (SDN) 23 Marapalam Padang with advice on how to use the Fones teeth brushing technique. Educational activity was carried out on January 16, 2023 with a total of 87 students. The stages of implementing this activity are preparation by conducting a preliminary study to the school, the implementation of counseling, namely oral health education with PowerPoint presentation media, posters, dental phantoms and toothbrushes followed by correct tooth brushing practices accompanied by the lecturers and students of the Faculty of Dentistry, Andalas University. There was a significant increase in students' understanding of healthy teeth, the benefits of brushing teeth, brushing time, and increasing children's skills in practicing toothbrushing with good and correct Fones techniques after education was provided. In order to maintain and improve oral health, it is suggested that this activity be repeated on a regular basis with different topics to increase students' knowledge of oral health science.